Mesenchymal stem cell-based tissue regeneration therapies for periodontitis - Ouchi, Takehito; Nakagawa, Taneaki (Regenerative therapy, 2020)
Periodontitis is commonly observed and is an important concern in dental health. It is characterized by a multifactorial etiology, including imbalance of oral microbiota, mechanical stress, and systemic diseases such as diabetes mellitus. The current standard treatments for periodontitis include elimination of the microbial pathogen and application of biomaterials for treating bone defects. However, the periodontal tissue regeneration via a process consistent with the natural tissue formation process has not yet been achieved. Developmental biology studies state that periodontal tissue is composed of neural crest-derived ectomesenchyme. To elucidate the process of periodontal regeneration, it is essential to understand the developmental background and intercellular cross-talk. Several recent studies have reported the efficacy of transplantation of mesenchymal stem cells for periodontal tissue regeneration. In this review, we discuss the basic knowledge of periodontal tissue regeneration using mesenchymal stem cells and highlight the potential of stem cell-based periodontal regenerative medicine. •Neural crest cells regulate the development and homeostasis of periodontal tissues.•Dental mesenchymal stem cells (MSCs) are used for treating alveolar bone defects.•Non-odontogenic MSCs can be investigated for periodontal tissue regeneration.•Using appropriate growth factors and scaffold may improve periodontium regeneration.